Exploring expatriate adjustment through identity perspective. Issue 3 (June 2020) - Peltokorpi, Vesa; Zhang, Ling Eleanor
Highlights: This study uses the identity theory to reveal multifaceted identities experienced by corporate expatriates. This study shows how these multifaceted identities are related to the mode/degree of expatriate adjustment. This study shows that these multifaceted identities through identity stability/change are related to expatriate adjustment. Abstract: This study reveals multifaceted identities experienced by corporate expatriates and how these identities are related to expatriate host country work and non-work adjustment. Specifically, we take a symbolic interactionism-based identity theory perspective and examine qualitative data from 73 corporate expatriates in China and Japan, revealing an expatriate identity (i.e., identification with being a manager and a foreigner), and a cultural identity (i.e., identification with home and host country cultures) which through identity stability/change are related to the mode and degree of expatriate work and non-work adjustment. Our findings suggest that these identities explain how corporate expatriates shape their new environment to their preferences, instead of adjusting to it.